The physiological role of glucagon-like peptide-1 in the regulation of renal function - Farah, Lívia X. S. (Am J Physiol Renal Physiol, 2015)
Glucagon like peptide-1 (GLP-1) is an incretin hormone constantly secreted from the intestine at low basal levels in the fasted state; plasma concentrations rise rapidly after nutrient ingestion. Upon release, GLP-1 exerts insulinotropic effects via a G protein-coupled receptor, stimulation of adenylyl cyclase, and cAMP generation. Although primarily involved in glucose homeostasis, GLP-1 can induce diuresis and natriuresis when administered in pharmacological doses in humans and rodents. However, whether endogenous GLP-1 plays a role in regulating renal function remains an open question. This study aimed to test the hypothesis that blockade of GLP-1 receptor (GLP-1R) signaling at baseline influences renal salt and water handling. To this end, the GLP-1R antagonist exendin-9 (100 μg·kg(−1)·min(−1)) or vehicle was administered intravenously to overnight-fasted male Wistar rats for 30 min. This treatment reduced urinary cAMP excretion and renal cortical PKA activity, demonstrating blockade of renal GLP-1R signaling. Exendin-9-infused-rats exhibited reduced glomerular filtration rate, lithium clearance, urinary volume flow, and sodium excretion compared with vehicle-infused controls. Exendin-9 infusion also reduced renal cortical Na(+)/H(+) exchanger isotope 3 (NHE3) phosphorylation at serine 552 (NHE3pS552), a PKA consensus site that correlates with reduced transport activity. Collectively, these results provide novel evidence that GLP-1 is a physiologically relevant natriuretic factor that contributes to sodium balance, in part via tonic modulation of NHE3 activity in the proximal tubule.